2006
DOI: 10.1123/tsp.20.2.222
|View full text |Cite
|
Sign up to set email alerts
|

Women in Coaching

Abstract: The purpose of this article is to review the challenges that women coaches must overcome and to discuss coach education strategies for facilitating the development of women coaches. Changes in representation of women in positions of leadership in sport have created a social context in which the experience of female coaches is referenced from a predominantly male perspective. As such, recurring issues elicited by attendees at the USOC/NCAA sponsored Women in Coaching Conferences are discussed. Coach education s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
97
2
24

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(138 citation statements)
references
References 16 publications
15
97
2
24
Order By: Relevance
“…Regarding the latter, we found that our participants valued receiving help and support, but sometimes they did not obtain them. Previous research has highlighted the relevance that having mentors has for women in order to gain confidence and experience both in their role as sport managers (e.g., IOC, 2010;Weaver & Chelladurai, 1999) or coaches (e.g., Allen & Shaw, 2009;Kilty, 2006). In this line, the current study reinforces the conclusions regarding mentoring stated in past research.…”
Section: Discussionsupporting
confidence: 82%
“…Regarding the latter, we found that our participants valued receiving help and support, but sometimes they did not obtain them. Previous research has highlighted the relevance that having mentors has for women in order to gain confidence and experience both in their role as sport managers (e.g., IOC, 2010;Weaver & Chelladurai, 1999) or coaches (e.g., Allen & Shaw, 2009;Kilty, 2006). In this line, the current study reinforces the conclusions regarding mentoring stated in past research.…”
Section: Discussionsupporting
confidence: 82%
“…The research informs us of women coaches having to work much harder to prove themselves than male colleagues, to other coaches, to their organisation or governing body, or to athletes (e.g. Norman, 2010;Rankin-Wright, 2015;Kilty, 2006). This is because the cultural perceptions of women, based on biological and natural assumptions, are juxtaposed to perceptions of what is a leader.…”
Section: Social Acceptancementioning
confidence: 99%
“…This is because the cultural perceptions of women, based on biological and natural assumptions, are juxtaposed to perceptions of what is a leader. In her review of the challenges that women coaches experience, Kilty (2006) found participants reported an unequal assumption of competence compared to male colleagues. Such covert discrimination was also a contributory factor in women's turnover intentions in Lovett and Lowry's (1997) study.…”
Section: Social Acceptancementioning
confidence: 99%
See 1 more Smart Citation
“…Obstáculos similares aos encontrados nessa pesquisa também foram verificados na literatura internacional, como o questionamento da competência feminina, a contratação por princípio da similaridade, ou seja, homens tendem a contratar homens, a homofobia, a falta de contatos para facilitar o acesso ao posto, o conflito da vida pessoal com a profissão, a falta de aceitação e credibilidade com os atletas, a ausência de outras mulheres em seu contexto, a dificuldade de ascensão de mulheres na carreira em categorias de base para categorias profissionais, e o fato de a atuação como treinadora em alguns casos ser voluntária, gerando incompatibilidade com a profissão que realmente exercem [16][17][25][26][27] . As participantes (n=11) afirmaram que a presença majoritária de homens no comando esportivo constitui uma barreira para a atuação delas.…”
Section: Resultsunclassified